Factors Related To Examination of IVA In Reproductive Women - Fitri, Laila; Febriyanti, Hellen; Sanjaya, Riona (Utan Kayu Publishing, 2021)
Cervical cancer is a cancer that occurs in the cervix, which is the area of the female reproductive organ which is the entrance to the uterus, located between the uterus (uterus) and the female intercourse (vagina). The incidence of cervical cancer can be detected by the method of Visual Inspection of Acetic Acid (IVA), the IVA examination aims to find pre-cancerous cervical lesions before they become cancerous. The research objective is to know the factors associated with IVA examination in fertile-aged women couples in the work area of Karya Tani Labuhan Maringgai Health Center, East Lampung Regency in 2021.This type of quantitative research with cross sectional approach. The population of this study were all WUS III with a sample of 98 respondents. the object of this research is the IVA examination. The research was conducted in the work area of Karya Tani Labuhan Maringgai Community Health Center, East Lampung Regency in April 2021. Data collection used a questionnaire. Univariate and bivariate (chi square) data analysis. The results showed that there was a relationship between knowledge and IVA examination in the work area of the Karya Tani Labuhan Maringgai Community Health Center in East Lampung Regency in 2021 (p-value = 0.018, OR = 6,000). There is a socio-cultural relationship to IVA examination in the work area of Karya Tani Labuhan Maringgai Health Center, East Lampung Regency in 2021 (p-value = 0.002, OR = 7.333). There is a relationship between family / husband support for IVA examination in the work area of the Karya Tani Labuhan Maringgai Community Health Center, East Lampung Regency in 2021 (p-value 0.004, OR = 5.760). There is no relationship between health care workers' support for IVA examinations in the work area of Karya Tani Labuhan Maringgai Community Health Center, East Lampung Regency in 2021 (p-value = 0.383). Suggestions to IVA officers are expected to take a personal approach to women of reproductive age couples so that they want to do IVA examinations